Motivation in Foreign Language Classrooms at Tertiary Level: A Case Study (Journal of Contemporary Educational Policies and Practices, 2021)
In teaching and learning a foreign language, especially English, motivation plays an extremely integral part in ensuring success. In this study, the researchers attempt to provide an overview of research on motivation and discover how motivation can assist second or foreign language learning in classrooms of English-majored students in the university setting. This study aims to investigate whether English-majored learners are motivated in learning English or not, focusing on extrinsic motivational factors to identify the factors to develop their motivation and maintain their journey of learning English. A questionnaire is devised and administered to 52 senior English-majored students. The data was then analyzed using the SPSS version 20. The results suggest that learners’ motivation is related to learning facilities and teacher’s personality which can encourage learners to think more positively and thus be more motivated in their language learning process. Along with providing specific recommendations for further research on motivation, the paper concludes by calling on for adopting a range of motivational factors that can promote English as a foreign or second language learning.
Keywords: foreign language, motivation, English-majored students, university, extrinsic motivation, motivational factors